The therapeutic potential of royal jelly in benign prostatic hyperplasia. Comparison with contemporary literature. (2nd July 2016) - Pajovic, Bogdan; Radojevic, Nemanja; Dimitrovski, Antonio; Tomovic, Savo; Vukovic, Marko
Abstract: The aim of this study is to establish the scientific benefit of royal jelly (RJ) on prostatic-specific antigen (PSA), post-void residual (PVR) volume and International Prostate Symptom Score (IPSS) in benign prostatic hyperplasia. For the study, a group of 40 men were administered 38 mg of RJ over a period of three months, their PSA values, prostate volumes and the volumes of their transitory prostate zones, PVR and IPPS values were measured at the end of the first month, and at the end of the third month. The results of this study confirm the potential of RJ in reducing PSA scores and improving IPSS values. Since the use of RJ did not lead to any significant reduction in PVR, prostate volume, or to any involution of the transitory zone, it appears that it may only affect the blood marker of prostatic hyperplasia and to improve quality-of-life (QoL) in those patients. Overall, in comparison to phytotherapy and conventional therapy, RJ had similar positive effects on QoL in patients with BPH, however it exhibited markedly better effects on reducing PSA levels in blood. The therapeutical use of RJ exhibited no side effects.